Natriuretic Peptide Signaling via Guanylyl Cyclase (GC)-A: An Endogenous Protective Mechanism of the Heart - Kishimoto, Ichiro (Bentham Science Publishers Ltd., 2009)
Atrial and brain natriuretic peptides (ANP and BNP, respectively) are cardiac hormones, secretions of which are markedly upregulated during cardiac failure, making their plasma levels clinically useful diagnostic markers. ANP and BNP exert potent diuretic, natriuretic and vasorelaxant effects, which are mediated via their common receptor, guanylyl cyclase (GC)-A (also called natriuretic peptide receptor (NPR)-A). Mice deficient for GC-A are mildly hypertensive and show marked cardiac hypertrophy and fibrosis that is disproportionately severe, given their modestly higher blood pressure. Indeed, the cardiac hypertrophy seen in these mice is enhanced in a blood pressure-independent manner and is suppressed by cardiomyocyte-specific overexpression of GC-A. These results suggest that the actions of a local cardiac ANP/BNP-GC-A system are essential for maintenance of normal cardiac architecture. In addition, GC-A was shown to exert its cardioprotective effects by inhibiting angiotensin II-induced hypertrophic signaling, and recent evidence suggests that regulator of G protein signaling (RGS) subtype 4 is involved in the GC-A-mediated inhibition of Gαq-coupled hypertrophic signal transduction. Furthermore, several different groups have reported that functional mutations in the promoter region of the human GC-A gene are associated with essential hypertension and ventricular hypertrophy. These findings suggest that endogenous GC-A protects the heart from pathological hypertrophic stimuli, and that humans who express only low levels of GC-A are genetically predisposed to cardiac remodeling and hypertension.